Women Drudgery Reduction in Hills Success story of Vivek millet Thresher cum Pearler - Singh, Sukhbir; Kharbikar, H. L.; Joshi, Pratibha; Sahoo, D. C.; Bisht, J. K. (Indian Farming, 2015)
Adoption and use of the millet thresher cum pearler technology in a collective way in the village of Uttarkashi and mechanized post harvest operations of millets of the whole village resulted in saving of 71- 72% and 45-47% cost of operation for threshing and dehusking, respectively and reduced lot of drudgery as compared to traditional system.